FORECASTING ELECTIONS: DO PREDICTION MARKETS TELLS US ANYTHING MORE THAN THE POLLS? - Davis, Brent (International Journal of Research -GRANTHAALAYAH, 2017)
Election forecasting is an expanding domain within political science, moving from the outer edges (as a novelty pursued by a few ‘quants’) toward the mainstream of the discipline. Amongst the most high profile of election forecasting techniques are prediction markets and vote-intention polls. While the weight of scholarly opinion appears to favour prediction markets over polls for election forecasting, there remain challengers and critics. This article joins with the challengers and the critics, looking at whether this ‘horse race’ competition between election forecasting approaches is valid. Using data from the 2013 Australian federal election, we conclude such comparisons-of-forecasts are misplaced in the Australian context, as prediction markets and vote-intention polls appear to be independent of each other given information from one appears to have no impact on the other.